Analisis Peran Dan Fungsi Badan Pengawasan Pemilihan Umum Kabupaten OKU Timur Dalam Pilkada tahun 2020 - Dian Ayu Wulandari; Achmad Akmaluddin (Yayasan Literasi Sains Indonesia, 2022)
The Election Supervisory Board has the authority to supervise and prevent violations in the election of regional heads who aim to be able to carry out decisive, effective and fair justice. The issue in which the Electoral Supervisory Board found reports of alleged violations as many as 20 alleged violation. Purpose of the research is to find out how the role and function of the Election Supervisory Board of Ogan Komering Ulu Timur Regency in the 2020 regional head elections. The research method uses qualitative research that aims to obtain a decripive analysis. The data is obtained through interview techniques, observations, literature and documentation. The research was conducted on April 26, 2021-May 20, 2021. Based on the results of the data, it can be known that the Election Supervision Agency of Ogan Komering Ulu Timur Regency has carried out its function and authority duties according to Law number 10 of 2016 concerning regional head elections seen from 6 aspects, namely a) the Election Supervision Agency coordinates and monitors the establishment of ad hoc election committees, stakeholders, communities and participatory supervision. b) evaluation, implementation of stakeholder organizers, local governments, police, winning teams of candidate couples, religious leaders, community leaders and community participation. c) receiving reports includes: alleged violations of electoral crimes, code of conduct, money politic, neutralist. d) facilities are obtained through capital from the budget of state revenue and expenditure from the government. e) receiving and following up on the report, the Election Supervision Agency received 20 alleged violations and 8 in follow-up in following up the report seen from because of the limited time of a short seven days in the handling of violations causing not all to go well as scheduled. f) follow up on recommendations and/or rulings using legal grounds, and regional head election laws.